2004
DOI: 10.1002/cncr.20533
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Fas ligand in retinoblastoma

Abstract: BACKGROUND The importance of the Fas‐Fas ligand (FasL) mechanism for the immune evasion by tumors provided a strong rationale for the examination of FasL expression in retinoblastoma. In an earlier publication, the authors reported that invasive retinoblastomas decreased Fas expression. Because to the authors' knowledge there is not much information regarding the effect of FasL expression on retinoblastoma, the authors studied the expression of FasL in retinoblastoma and correlated it with invasiveness. METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Additional studies at our institute have shown that there are multiple mechanisms in retinoblastoma that contribute to their invasiveness: Invasive retinoblastoma had 1) decreased metastasis‐suppressor protein nm23‐H1 and nm‐H255; 2) decreased tetraspanin protein KAI1/CD82,56 which contributes to increased motility of tumor cells and to invasion; 3) decreased/absent Fas expression,57 which allows tumor cells to escape from Fas ligand (FasL)‐mediated tumor cell death; 4) elevated FasL expression in invading tumors that may enable them to lyse Fas‐expressing tumor‐infiltrating lymphocytes58; and 5) decreased human leukocyte antigens Class I and II and the antigen‐processing molecules of the Class I pathway,59 which allows the escape of tumor cells from cytotoxic T lymphocyte‐mediated cell death while maintaining resistance to natural killer cell lysis. Hence, these deregulations allow tumors to gain time for the accumulation of critical mutations and/or derangements in the expression of malignancy causing genes, which will provide these tumors with uncontrollable invasive potential.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies at our institute have shown that there are multiple mechanisms in retinoblastoma that contribute to their invasiveness: Invasive retinoblastoma had 1) decreased metastasis‐suppressor protein nm23‐H1 and nm‐H255; 2) decreased tetraspanin protein KAI1/CD82,56 which contributes to increased motility of tumor cells and to invasion; 3) decreased/absent Fas expression,57 which allows tumor cells to escape from Fas ligand (FasL)‐mediated tumor cell death; 4) elevated FasL expression in invading tumors that may enable them to lyse Fas‐expressing tumor‐infiltrating lymphocytes58; and 5) decreased human leukocyte antigens Class I and II and the antigen‐processing molecules of the Class I pathway,59 which allows the escape of tumor cells from cytotoxic T lymphocyte‐mediated cell death while maintaining resistance to natural killer cell lysis. Hence, these deregulations allow tumors to gain time for the accumulation of critical mutations and/or derangements in the expression of malignancy causing genes, which will provide these tumors with uncontrollable invasive potential.…”
Section: Discussionmentioning
confidence: 99%
“…Collect different experimental groups cells and label Fas antibody according to the method in [2,3] when Fas was labeled. Then Fas expression was detected by FCM.…”
Section: ) Detection Of Fas Expression By Fcm After Jurkat T Cells Wmentioning
confidence: 99%
“…CTLinduced apoptosis of cancer cells via Fas pathway is one of the two main ways of CTL killing cancer cells in human body, the other is perforin-based [1]. Some reports found that cancer cells could decrease Fas expression which could escape the immune surveillance and killing, on the other hand, functional FasL expression by certain cancer cell types could induce apoptosis of CTL, especially tumor specific antigen induce Fas-bearing tumor infiltrating lymphocytes (TILs), because they exhibited significantly increased expression of Fas relative to peripheral blood lymphocytes [2][3][4]. In these cases, Fas and FasL may contribute to tumor immune privilege by inducing FasLmediated apoptosis of host CTL and natural killer (NK) cells.…”
Section: Introductionmentioning
confidence: 99%